Soft Skills for Sustainable Development in Tourism: The Bulgarian Experience - Kiryakova-Dineva, Teodora; Kyurova, Vyara; Chankova, Yana (European Journal of Sustainable Development, 2019)
The aim of this paper is to discuss the soft skills acquisition in the tourism industry as a means of education for sustainable development. A quantitative research approach has been applied in order to investigate the soft skills needed for tourism. The analysis is based on interviews carried out with representatives of the Bulgarian regional Chamber of Commerce and representatives of the Bulgarian hotel and restaurant industry. Additionally, a case study involving three groups of respondents, i.e. Learners, Educators and Representatives of business and Employers in the tourism and hospitality industry in Bulgaria was conducted based on a combined list of soft skills. Whereas some hard skills are traditionally taught at the educational institutions, soft skills, here identified as Core soft skills, Specific soft skills and Managerial soft skills, often remain beyond the educators’ aims. Thus, the study provides some useful insights into the contemporary practice of tourism and hospitality education, on the one hand, and into the paradigm of education for sustainable development, on the other. Keywords: Soft Skills, Tourism, Business, Hospitality, Education, Sustainability, Bulgaria